Dynamics of prostaglandin E2 in the surgical treatment of gastroesophageal reflux disease - Haidarzhi, Ye. I.; Гайдаржі, Євген Іванович (Запорізький державний медичний університет, 2023)
The aim of the study is to evaluate the effect of antireflux surgery on the level of prostaglandin E2 in blood serum and to verify that its changes after surgical treatment are associated with the decrease of gastroesophageal reflux and esophageal inflammation. Materials and methods. 35 patients were examined with GERD who underwent laparoscopic total antireflux fundoplication. There were 26 women (74.3 %) and 9 men (25.7 %). Their age is 55.3 ± 11.3. The control group consisted of 20 practically healthy people (women – 14 (70.0 %), men – 6 (30.0 %), average age – 56.7 ± 10.6). Immunoenzymatic analysis of prostaglandin E2 was performed in blood plasma, which was obtained according to a standard method. Determination of prostaglandin E2 (Prostaglandin E2 ELISA, KGE004B, RnD Systems) was carried out by the immunoenzymatic method based on the use of the “sandwich“ variant of the solid-phase immunoenzymatic analysis. The procedure was carried out on the immunoenzyme complex ImmunoChem-2100 (USA) at the Department of Clinical Laboratory Diagnostics in Zaporizhzhia State Medical University. Research on the level of prostaglandin E2 in the main group was carried out before surgical treatment and 2–3 months after surgery by taking venous blood and using the above test systems. Statistical evaluation of the research results was performed using the Statistica for Windows 13 software package (StatSoft Inc., No. JPZ804I382130ARCN10-J). Results. The level of prostaglandin E2 in the blood of practically healthy people was 16.7 ± 6.1 pg/ml. In the main group, the values of prostaglandin E2 before surgical treatment were 25.8 ± 5.7 pg/ml, after surgical treatment, they decreased to 13.5 ± 5.3 pg/ml. The detailed analysis of patients in the main group showed that the level of prostaglandin E2 did not differ statistically in different erosive forms of esophagitis, or CLE and NERD. But it is statistically different from the level of prostaglandin E2 in practically healthy individuals of the control group. The conducted correlation analysis indicated that the level of prostaglandin E2 did not depend on the duration of acid exposure in the esophagus, as well as on the severity of esophagitis or the presence of CLE. Мета роботи – оцінити вплив антирефлюксної операції на рівень простагландину Е2 в сироватці крові та переконатися, що його зміни після хірургічного лікування пов’язані зі зменшенням гастроезофагеального рефлюксу та запалення стравоходу. Матеріали та методи. Обстежили 35 пацієнтів із ГЕРХ, яким виконали лапароскопічну тотальну антирефлюксну фундоплікацію (26 (74,3 %) жінок, 9 (25,7 %) чоловіків). Вік пацієнтів становив 55,3 ± 11,3 року. В контрольну групу залучили 20 практично здорових осіб (14 (70,0 %) жінок, 6 (30,0 %) чоловіків), середній вік – 56,7 ± 10,6 року. Імуноферментне дослідження простагландину Е2 здійснили в плазмі крові, яку одержали за стандартною методикою. Простагландин E2 (Prostaglandin E2 ELISA, KGE004B, RnD Systems) визначили імуноферментним методом, що базується на використанні «сендвіч»-варіанта твердофазного імуноферментного аналізу. Процедуру здійснили на імуноферментному комплекcі ImmunoChem-2100 (США) на кафедрі клінічної лабораторної діагностики Запорізького державного медичного університету. Дослідження рівня простагландину Е2 в основній групі здійснили до оперативного лікування та через 2–3 місяці після операції шляхом забору венозної крові та використання названих тест-систем. Статистично результати дослідження оцінили, застосувавши програмний пакет Statistica for Windows 13 (StatSoft Inc., ліцензія № JPZ804I382130ARCN10-J). Результати. У практично здорових осіб рівень простагландину Е2 у крові становив 16,7 ± 6,1 пг/мл. В основній групі значення простагландину Е2 до хірургічного лікування дорівнювали 25,8 ± 5,7 пг/мл, після нього знизилися до 13,5 ± 5,3 пг/мл. Детальний аналіз структури основної групи показав, що рівень простагландину Е2 статистично не відрізнявся в пацієнтів із різними ерозивними формами езофагіту, CLE і неерозивною рефлюксною хворобою. Статистично вірогідну різницю визначили щодо рівня простагландину Е2 у практично здорових осіб контрольної групи. Кореляційний аналіз показав, що рівень простагландину Е2 не залежить від тривалості кислотної експозиції в стравоході, а також від ступеня тяжкості езофагіту чи наявності CLE.
Динаміка простагландину Е2 при хірургічному лікуванні гастроезофагеальної рефлюксної хвороби
ORCID ID: 0000-0001-7211-1795
Keywords: gastroesophageal reflux disease; hiatal hernia; prostaglandin E2; гастроезофагеальна рефлюксна хвороба; грижа стравохідного отвору діафрагми; простагландин Е2